ESPEN guideline on clinical nutrition in liver disease. Issue 2 (April 2019) - Plauth, Mathias; Bernal, William; Dasarathy, Srinivasan; Merli, Manuela; Plank, Lindsay D.; Schütz, Tatjana; Bischoff, Stephan C.
Summary: This update of evidence-based guidelines (GL) aims to translate current evidence and expert opinion into recommendations for multidisciplinary teams responsible for the optimal nutritional and metabolic management of adult patients with liver disease. The GL was commissioned and financially supported by ESPEN. Members of the guideline group were selected by ESPEN. We searched for meta-analyses, systematic reviews and single clinical trials based on clinical questions according to the PICO format. The evidence was evaluated and used to develop clinical recommendations implementing the SIGN method. A total of 85 recommendations were made for the nutritional and metabolic management of patients with acute liver failure, severe alcoholic steatohepatitis, non-alcoholic fatty liver disease, liver cirrhosis, liver surgery and transplantation as well as nutrition associated liver injury distinct from fatty liver disease. The recommendations are preceded by statements covering current knowledge of the underlying pathophysiology and pathobiochemistry as well as pertinent methods for the assessment of nutritional status and body composition.